Gut microbiota compositional and functional fingerprint in patients with alcohol use disorder and alcohol‐associated liver disease. (3rd February 2020) - Addolorato, Giovanni; Ponziani, Francesca R.; Dionisi, Tommaso; Mosoni, Carolina; Vassallo, Gabriele A.; Sestito, Luisa; Petito, Valentina; Picca, Anna; Marzetti, Emanuele; Tarli, Claudia; Mirijello, Antonio; Zocco, Maria Assunta; et al.
Abstract: Background & aims: Alcohol use disorder (AUD) represents the most common cause of liver disease. The gut microbiota plays a critical role in the progression of alcohol‐related liver damage. Aim of this study was to characterize the gut microbial composition and function in AUD patients with alcohol‐associated liver disease (AALD). Methods: This study included 36 AUD patients (14 with cirrhosis) who were active drinkers and an equal number of matched controls. Stool microbial composition, serum levels of lipopolysaccharide, cytokines/chemokines and gut microbiota functional profile were assessed. Results: AUD patients had a decreased microbial alpha diversity as compared to controls (0.092 vs 0.130, P = .047) and a specific gut microbial signature. The reduction of Akkermansia and the increase in Bacteroides were able to identify AUD patients with an accuracy of 93.4%. Serum levels of lipopolysaccharide (4.91 vs 2.43, P = .009) and pro‐inflammatory mediators (tumour necrosis factor alpha 60.85 vs 15.08, P = .001; interleukin [IL] 1beta 4.43 vs 1.72, P = .0001; monocyte chemoattractant protein 1 225.22 vs 16.43, P = .006; IL6 1.87 vs 1.23, P = .008) were significantly increased in AUD patients compared to controls and in cirrhotic patients compared to non‐cirrhotic ones (IL6 3.74 vs 1.39, P = .019; IL8 57.60 vs 6.53, P = .004). The AUD‐associated gut microbiota showed an increased expression of gamma‐aminobutyric acid (GABA) metabolic pathways and energy metabolism. Conclusions: AUD patients present a specific gut microbial fingerprint, associated with increased endotoxaemia, systemic inflammatory status and functional alterations that may be involved in the progression of the AALD and in the pathogenesis of AUD.